Anteroposterior condylar position: A comparative study between subjects with normal occlusion and patients with Class I, Class II Division 1, and Class III malocclusions - Fraga, Marcelo Reis (International Scientific Literature, Inc., 2013)
BACKGROUND: The present study aimed to determine and compare the anteroposterior position of the condyle in the mandibular fossa between groups of asymptomatic subjects with normal occlusion and asymptomatic subjects with Class I, Class II Division 1, and Class III malocclusions. MATERIAL/METHODS: Thirty persons with normal occlusion, 30 with Class I malocclusion, 30 with Class II Division 1, and 30 with Class III had computed tomography scans of their temporomandibular joints. The anterior joint space/posterior joint space (AJS/PJS) ratio was determined for the right and left joints. The paired t test was used to analyze the AJS/PJS ratio between both sides for each group. The ANOVA test was applied to verify the differences between the groups for the measurements of the right and left sides. In case the ANOVA test confirmed significance, the Dunnett’s t test was performed to compare the groups of malocclusion with that of normal occlusion. RESULTS: The paired t test between the AJS/PJS relationships in the right and left sides showed the following p values: Class I (0.168), Class II Division 1 (0.662), Class III (0.991), and normal occlusion (0.390). The ANOVA test showed a p value of 0.445 for the comparisons of the right side and 0.040 for the left side. The Dunnett’s t test demonstrated a statistically significant difference between the Class II group and the normal occlusion group (p value of 0.026) in the joints of the left side. CONCLUSIONS: Bilateral symmetry and lack of condyle centralization were common characteristics among all groups. The greatest condylar decentralization was observed in the Class II group, whereas the least condylar decentralization was found in the normal occlusion group.